Cash Use Across Countries and the Demand for Central Bank Digital Currency - Khiaonarong, Tanai; Humphrey, David (Washington, D.C. : International Monetary Fund, 2019)
The level and trend in cash use in a country will influence the demand for central bank digital currency (CBDC). While access to digital currency will be more convenient than traveling to an ATM, it only makes CBDC like a bank debit card-not better. Demand for digital currency will thus be weak in countries where cash use is already very low, due to a preference for cash substitutes (cards, electronic money, mobile phone payments). Where cash use is very high, demand should be stronger, due to a lack of cash substitutes. As the demand for CBDC is tied to the current level of cash use, we estimate the level and trend in cash use for 11 countries using four different measures. A tentative forecast of cash use is also made. After showing that declining cash use is largely associated with demographic change, we tie the level of cash use to the likely demand for CBDC in different countries. In this process, we suggest that one measure of cash use is more useful than the others. If cash is important for monetary policy, payment instrument competition, or as an alternative payment instrument in the event of operational problems with privately supplied payment methods, the introduction of CBDC may best be introduced before cash substitutes become so ubiquitous that the viability of CBDC could be in doubt.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet